2017
DOI: 10.1007/s10815-017-1084-2
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the size of the placenta and umbilical cord between women with natural pregnancy and those with IVF pregnancy

Abstract: PurposeThe purpose of this study was to compare the sizes of the placenta and umbilical cord in women with natural pregnancy versus those undergoing in vitro fertilization (IVF).MethodsOverall, 1610 cases of uncomplicated single pregnancies with vaginal delivery at ≥ 37 weeks of gestation were included in this study. The patients were divided into two groups: natural pregnancy group (n = 1453) and IVF pregnancy not including intracytoplasmic sperm injection (ICSI) treatment (n = 157). The groups were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
(21 reference statements)
4
24
0
Order By: Relevance
“…By birth, iVF-eT placentas were found to be heavier than the control group (76). likewise, placentas in humans following iVF-eT were overrepresented in the highest quartile of weight, and the placenta weight/birth weight ratio was frequently higher even after adjusting for potential confounding factors (77). a larger placenta is not necessarily synonymous with a higher efficiency in oxygen and nutrient transfer.…”
Section: Discussionmentioning
confidence: 89%
“…By birth, iVF-eT placentas were found to be heavier than the control group (76). likewise, placentas in humans following iVF-eT were overrepresented in the highest quartile of weight, and the placenta weight/birth weight ratio was frequently higher even after adjusting for potential confounding factors (77). a larger placenta is not necessarily synonymous with a higher efficiency in oxygen and nutrient transfer.…”
Section: Discussionmentioning
confidence: 89%
“…multiple pregnancies. The incidence of VCI was reported to be low among singleton pregnancies, ranging from 0.4% [9] to 11.0% [41], with 11.0% appearing to be an outlier, given the second highest reported incidence value being 3.6% [41]. Incidence was reported to be higher in twin pregnancies (Fig.…”
Section: Epidemiologymentioning
confidence: 94%
“…2). VCI was reported to have a strong association with low cord insertion [39], a variable (weak to strong) association with in vitro fertilisation (IVF) [4,7,8,41], a moderate association with placenta praevia [4,7,8] and a weak to moderate association with nulliparity [3,8] (Fig. 2).…”
Section: Epidemiologymentioning
confidence: 99%
“…Human cohort and population studies have either found higher placental weight 30,38 or placental weights that are not significantly different between ART and non-ART pregnancies. [39][40][41][42] While increased placental weight may not be an outcome of all ART-conceived pregnancies, for those ART pregnancies that do result in increased placental weight, it may represent a biologically meaningful outcome with short-and long-term health implications for the offspring. Thus, an important theme of this review is that investigating the underlying mechanisms and consequences involved in ART pregnancies that do result in placental macroscopic, microscopic, and/or molecular abnormalities cannot be ignored.…”
Section: Morphological Phenotypesmentioning
confidence: 99%